New Acetohydrazides Incorporating 2‐Oxoindoline and 4‐Oxoquinazoline: Synthesis and Evaluation of Cytotoxicity and Caspase Activation Activity. Issue 3 (4th February 2020) - Huan, Le Cong; Anh, Duong Tien; Truong, Bui Xuan; Duc, Phan Huy; Hai, Pham‐The; Duc‐Anh, Lai; Huong, Le‐Thi‐Thu; Park, Eun Jae; Lee, Hye Jin; Kang, Jong Soon; Tran, Phuong‐Thao; Thanh Hai, Dinh Thi; et al.
Abstract: In our search for new small molecules activating procaspase‐3, we have designed and synthesized a series of new acetohydrazides incorporating both 2‐oxoindoline and 4‐oxoquinazoline scaffolds. Biological evaluation showed that a number of these acetohydrazides were comparably or even more cytotoxic against three human cancer cell lines (SW620, colon cancer; PC‐3, prostate cancer; NCI−H23, lung cancer) in comparison to PAC‐1, a first procaspase‐3 activating compound, which was used as a positive control. One of those new compounds, 2‐(6‐chloro‐4‐oxoquinazolin‐3(4 H )‐yl)‐ N ′‐[(3 Z )‐5‐methyl‐2‐oxo‐1, 2‐dihydro‐3 H ‐indol‐3‐ylidene]acetohydrazide activated the caspase‐3 activity in U937 human lymphoma cells by 5‐fold higher than the untreated control. Three of the new compounds significantly induced necrosis and apoptosis in U937 cells. Abstract :